“It’s God’s work”: a multiple case study of the use of the Bible in the movement to end poverty led by the poor - Williams, Jessica Chadwick (Kansas State University, 2022)
While the Bible is often used as justification for systems that create and maintain poverty and blame the poor for their poverty, within the movement to end poverty led by the poor the Bible is understood as a liberatory text and a guide to organizing to end poverty. The purpose of this research was to understand how poor people’s organizations in the movement to end poverty led by the poor in the U.S. engage the Bible in their organizing. The study was grounded in the theories and praxis of the movement to end poverty led by the poor in the U.S. and situated within the field of social movement learning. Research was conducted using multiple, qualitative case study methodology to research three poor people’s organizations within the movement to end poverty led by the poor which were geographically, religiously, and culturally diverse and focused on different key issues in their work to end poverty including, housing and homelessness, tenant rights and immigration, and the right to a living wage and a union. Findings revealed the influence of the local historical, religious, and political contexts on how the organizations engage the Bible. Additionally, the three organizations utilized similar interpretative techniques in engaging with the biblical text, including beginning with the lived experiences of the poor in their communities and the identification and exploration of characters and conditions in the biblical text with parallels to the realities and lived experiences of the poor within the organizations. The findings suggest poor people’s organizations in the movement to end poverty led by the poor in the U.S. engage the Bible ideologically, materially, and spiritually through pedagogies analogous to those within the biblical text and through a model of dialectical, pedagogical relationships which include learning, education, organizing, and leadership development.
Keywords: Bible; Poverty; Social movement learning; Social movement organizing